Transcription from Fusion Promoters Generated during Transposition of Transposon Tn4652 Is Positively Affected by Integration Host Factor in Pseudomonas putida - Teras, Riho (American Society for Microbiology, 2000)
We have previously shown that both ends of the Tn3 family transposon Tn4652 contain integration host factor (IHF) binding sites and that IHF positively regulates expression of the Tn4652 transposase gene tnpA in Pseudomonas putida (R. Hõrak, and M. Kivisaar, J. Bacteriol. 180:2822–2829, 1998). Tn4652 can activate silent genes by creating fusion promoters during the transposition. The promoters are created as fusions between the −35 hexamer provided by the terminal inverted repeats of Tn4652 and the −10 hexamers in the target DNA. Two fusion promoters, PRA1 and PLA1, that contain sequences of the right and left termini of Tn4652, respectively, were chosen for the study of mechanisms of transcription activation. Gel mobility shift analysis using crude extracts from P. putida cells allowed us to detect specific binding of P. putida IHF to the ends of the transposon Tn4652. We found that the rate of transcription from the fusion promoter PRA1 is enhanced by IHF. Notably, the positive effect of IHF on transcription from the promoter PRA1 appeared only when cells of P. putida reached the stationary growth phase. We speculate that the intracellular concentration of IHF might be critical for the in vivo effect of IHF on transcription from the fusion promoters in P. putida. In the case of PLA1, the mechanism of transcription modulation by IHF is different than that observed for PRA1. Our results demonstrate that transcription of neighboring genes from outwardly directed promoters at the ends of a mobile DNA element could be influenced by the same factors that control transposition of the element.